2023
DOI: 10.1186/s12905-023-02392-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of depression, syndemic factors and their impact on viral suppression among female sex workers living with HIV in eThekwini, South Africa

Abstract: Introduction Over half of female sex workers (FSW) in South Africa are living with HIV and clinical depression has been frequently documented among FSW. Data characterizing structural determinants of depression and the role of syndemic theory, synergistically interacting disease states, on viral suppression among FSW in South Africa are limited. Methods Between July 2018-March 2020, non-pregnant, cisgender women (≥ 18 years), reporting sex work as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Bhardwaj et al. (2023) 24 employed a viral load threshold of ≥50 copies/mL to examine factors associated with VNS among female sex workers aged 18 years and above. In contrast, Nyakato et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhardwaj et al. (2023) 24 employed a viral load threshold of ≥50 copies/mL to examine factors associated with VNS among female sex workers aged 18 years and above. In contrast, Nyakato et al.…”
Section: Resultsmentioning
confidence: 99%
“…Bhardwaj et al (2023) 24 employed a viral load threshold of ≥50 copies/ mL to examine factors associated with VNS among female sex workers aged 18 years and above. In contrast, Nyakato et al (2022) 44 and Goldman et al (2008) 29 utilised a viral load threshold of ≥400 copies/ mL to Investigate factors associated with VNS among adults.…”
mentioning
confidence: 99%
“…Most of the scales used were developed and validated in high income settings and therefore lacked contextual (cultural and non -specificity to the HIV population) validity. The reliability coefficient of the scales was not reported in a majority of the studies (n = 11) [6,26,29,30,32,33,35,[37][38][39]43].…”
Section: Mostly Used Depression and Anxiety Assessment Measuresmentioning
confidence: 95%
“…Other risk factors included loss of selfesteem, experiences of discrimination, loss of life partners and or other family members, poverty, educational status, victimization, living with people other than direct family members, homelessness, being single or divorced. In 11 of these studies [6,26,[28][29][30][31][32][33][41][42][43], a univariate, multivariate or logistic regression analysis showed that sexual abuse, physical intimate partner violence, loneliness, enacted stigma, childhood trauma, post-traumatic stress disorder, young age, high viral load, having no formal education, divorce, unemployment and low social support increased the odds of depression and anxiety in FLWHA and was statistically significant (P � 0.005). However, one study [36] showed there was no significant correlation (P � 0.005) between depression/anxiety symptoms and educational status, employment status, and ART treatment status.…”
Section: Risks Factors Of Mental Illness In Flwhamentioning
confidence: 99%
See 1 more Smart Citation